The Role of the IAIN Pontianak Futsal Community: Public Relations, Social Media, and Campus Promotion - Handes, Handes (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2025)
This study aims to determine the role of the IAIN Pontianak futsal community in public relations in using Instagram social media in promoting IAIN Pontianak in non-academic fields. This study uses qualitative research with a descriptive approach. Data collection techniques use interviews, observations, and documentation. The results of this study indicate that the IAIN Pontianak futsal community utilizes Instagram in promoting IAIN Pontianak's non-academic activities. Through social media at least inform the public that IAIN Pontianak has sports facilities such as futsal fields, holds futsal tournaments for children, schools, and the general public. There are three roles of the futsal community for IAIN Pontianak, namely, early age development in collaboration with the fafage academy Indonesia, holding futsal tournaments and participating in local, regional and national futsal tournaments, and building cooperation with sponsor partners. This study has limitations in qualitative research methods and a limited number of informants. Thus, further research can conduct a survey of the role of the futsal community on lecturers and students of IAIN Pontianak with quantitative research